EFFECT OF UNDERSTANDING FINANCIAL MANAGEMENT, REGIONAL FINANCIAL ACCOUNTING SYSTEMS, EFFECTIVENESS OF INTERNAL CONTROL, AND COMMITMENT TOWARDS FINANCIAL PERFORMANCE OF NORTH SULAWESI PROVINCE - Saerang, David Paul Elia; Wokas, Heince R. N.; Kumaat, Robby J.; Datu, Christian (Universitas Sam Ratulangi, 2019)
This study aims to determine, the effect of understanding financial management, regional financial accounting system, effectiveness of internal control and organizational commitment towards financial performance of region and city governments in the province of North Sulawesi. The type of this research is quantitative. The population are all Regional Work Unit (SKPD) government financial managers of North Sulawesi, the respondents are 125 respondents as financial managers namely PPK-SKPD, Head of Finance and Financial Staffs. The Data method is using questionnaires and the analysis is using multiple regression analysis. The result shows that the understanding of financial management and effectiveness of internal control have a significant effect to the financial performance, while the regional financial accounting system and organizational commitment are not significant.